Probiotics reshape microbial community assembly and functional stability in mud crab (Scylla paramamosain) larvae under high-temperature stress - Junqi Yu; Tong Li; Gengshen Wang; Jun Ling; Wei Wang; Xueyang Wang; Chunyan Yin; Ning Qiao; Chen Chen (Frontiers in Marine Science, 2026)
High-temperature stress threatens sustainable mud crab ( Scylla paramamosain ) aquaculture by destabilizing the larval microbiome and elevating mortality. This study investigates whether probiotic supplementation can modulate microbial community dynamics and functional assembly to enhance heat resilience. Mud crab larvae across four developmental stages (Zoea I to IV, Z1-Z4) were divided into three groups: a probiotic group (supplemented with Lactobacillus , LAC), an antibiotic group (ANT), and a control group (CK). The microbial community was analyzed by 16S rRNA gene sequencing. We then calculated α- and β-diversity indices, constructed co-occurrence networks, and inferred functional profiles using PICRUSt2 to assess the structural and functional responses to the treatments. The larval microbiome exhibited stage-specific structural shifts. Although the LAC group showed a significant reduction in α-diversity at the Z4 stage, it demonstrated higher temporal stability in community structure compared to the CK and ANT groups. Co-occurrence network analysis revealed that LAC simplified inter-taxa relationships by lowering modularity and increasing negative interactions, whereas ANT formed a more modular but less connected network. Deterministic processes dominated the functional assembly. The microbiota in the LAC group was significantly associated with enhanced carbohydrate and amino acid metabolism, while the ANT group up-regulated pathways related to stress response and antibiotic resistance. Our results demonstrate that probiotic Lactobacillus can remodel the microbial ecology of mud crab larvae under thermal stress, promoting a functionally stable and resilient microbiome. These findings provide a mechanistic foundation for employing probiotics to develop temperature-resilient aquaculture practices for S. paramamosain .